Modules with respect to cyclic purity - Mao, Lixin (MATHEMATICA SCANDINAVICA, 2011)
An exact sequence $0→ A→ B→ C→ 0$ of left $R$-modules is called cyclically pure if for every right ideal $I$ of $R$, the sequence $0→ (R/I)\otimes A → (R/I)\otimes B → (R/I)\otimes C → 0$ is exact. In this paper, we study some special modules with respect to cyclic purity, such as $CP$-projective, $CP$-injective and $CP$-flat modules.